2001
DOI: 10.1183/09031936.01.00067001
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of bronchial hyperresponsiveness in three selected areas in East Germany

Abstract: The prevalence of asthma, bronchial hyperresponsiveness (BHR) and allergic rhinitis in children was lower in East Germany compared to West Germany. The reasons for this difference are still not understood. This study tested the hypothesis that prevalence of BHR increased in East German children after reunification.Two consecutive cross-sectional surveys of schoolchildren aged 8–14 yrs from three communities in East Germany were carried out in 1992–1993 and 1995–1996. A subsample of 530 and 790 children with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…Considering all studies done there is no consistent trend for an increase of asthma prevalence or bronchial hyperresponsiveness [36,37]. Yet the overall prevalence of asthma in adults in the current study is slightly higher than comparable samples [13].…”
Section: Discussioncontrasting
confidence: 52%
“…Considering all studies done there is no consistent trend for an increase of asthma prevalence or bronchial hyperresponsiveness [36,37]. Yet the overall prevalence of asthma in adults in the current study is slightly higher than comparable samples [13].…”
Section: Discussioncontrasting
confidence: 52%
“…The results of these three studies consistently showed increasing prevalence for hay fever, atopic eczema and asthma, although not for asthma in the Leipzig study [19][20][21]. The increasing prevalence of asthma was supported by findings of the Bitterfeld Study [22], which found an increasing prevalence of bronchial hyperresponsiveness (BHR). Despite a certain heterogeneity of the results on temporal changes of allergic sensitization (table 4), the two studies showed consistently an increase in prevalence of allergic sensitization to birch pollen and house dust mites, whereas no [17,18] or even decreasing [22] tendencies were reported for grass pollen.…”
Section: Comparison With Other Studiessupporting
confidence: 60%
“…The increasing prevalence of asthma was supported by findings of the Bitterfeld Study [22], which found an increasing prevalence of bronchial hyperresponsiveness (BHR). Despite a certain heterogeneity of the results on temporal changes of allergic sensitization (table 4), the two studies showed consistently an increase in prevalence of allergic sensitization to birch pollen and house dust mites, whereas no [17,18] or even decreasing [22] tendencies were reported for grass pollen. Furthermore, both studies found a consistent increase of prevalence of strong allergic sensitization.…”
Section: Comparison With Other Studiesmentioning
confidence: 48%
See 1 more Smart Citation
“…Methods of pulmonary function measurements are described elsewhere (Frye et al 2001;Wjst et al 1998). Briefly, technicians were trained thoroughly at the beginning of each survey.…”
Section: Ambient Pollutionmentioning
confidence: 99%